Interactive Media in Enhancing Proficiency and Engagement in Arabic Language Learning - Andrew Aliffiansyah Ariyanto; Deny Tri Ardianto; Moh. Muchtarom (Jurnal Al-Maqoyis, 2026)
Arabic language learning continues to face challenges related to low student motivation and limited engagement due to traditional instructional approaches. This study aims to examine the significance of interactive media in enhancing Arabic language proficiency and learner engagement. Employing a qualitative library research design with a systematic literature review approach, this study analyzed peer-reviewed journal articles published between 2020 and 2025 focusing on interactive media, gamification, and technology-enhanced Arabic instruction. The findings indicate that interactive media including multimedia applications, digital games, and online learning platforms significantly contribute to improving students’ motivation, participation, and mastery of the four core language skills: listening, speaking, reading, and writing. Interactive environments that provide multimodal input and immediate feedback foster more active and meaningful learning experiences. This study highlights the pedagogical importance of integrating technology-based interactive tools to promote communicative competence and sustainable engagement in Arabic language education..